Designing a Web-Based Information System for Green Open Space Utilization Services - Nihayatur Rohmah; Yunianita Rahmawati; Uce Indahyanti; Nuril Lutvi Azizah (SaNa: Journal of Blockchain, NFTs and Metaverse Technology, 2026)
The development of an information system in this study was carried out to meet the needs of the Sidoarjo Regency Environment and Sanitation Agency (DLHK) for an integrated system. More specifically, this web-based system was designed to handle services related to the use of Green Open Spaces (RTH), which until now have been dependent on manual processes and have lacked data integration. This condition has the potential to hinder the optimization of management, supervision, and service quality. In building the system, the researchers chose the Waterfall method. The reason is that this method provides clear and sequential stages. We went through these stages, starting from analyzing user needs at DLHK, then designing the system and database, then programming using a specific language, then testing the system, and finally preparing maintenance documents. To ensure that the system runs well, two types of tests were conducted. The first test was a Black Box functional test with 27 scenarios created based on use case schemes. The second test was a User Acceptance Test (UAT) involving potential users to fill out questionnaires. The results of this series of tests were encouraging. In the Black Box test, 96.3% of the functions were recorded as successful. According to the researchers, this figure shows that almost all core features are functioning optimally. Meanwhile, in the UAT, the user satisfaction score reached 91%. Based on our interpretation, this score falls into the "very satisfied" category and proves that the system is well received at the end-user level.